"An Unpopular Cause": The Union of Australian Women's Support for Aboriginal Rights. (May 2019) - Milner, Lisa
Abstract : The Union of Australian Women (UAW) was a national organisation for left-wing women between World War II and the emergence of the women's liberation movement. Along with other left-wing activists, UAW members supported Aboriginal rights, through their policies, publications and actions. They also attracted a number of Aboriginal members including Pearl Gibbs, Gladys O'Shane, Dulcie Flower and Faith Bandler. Focusing on NSW activity in the assimilation period, this article argues that the strong support of UAW members for Aboriginal rights drew upon the group's establishment far-left politics, its relations with other women's groups and the activism of its Aboriginal members. Non-Aboriginal members of the UAW gave practical and resourceful assistance to their Aboriginal comrades in a number of campaigns through the assimilation era, forming productive and collaborative relationships. Many of their campaigns aligned with approaches of the Communist Party of Australia and left-wing trade unions. In assessing the relationship between the UAW and Aboriginal rights, this article addresses a gap in the scholarship of assimilation era activism.